2014
DOI: 10.1038/gene.2013.74
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium genetic loci linked to host cytokine and chemokine responses

Abstract: Both host and parasite factors contribute to disease severity of malaria infection; however, the molecular mechanisms responsible for the disease and the host-parasite interactions involved remain largely unresolved. To investigate effects of parasite factors on host immune responses and pathogenesis, we measured levels of plasma cytokines/chemokines (CC) and growth rates in mice infected with two Plasmodium yoelii strains having different virulence phenotypes and in progeny from a genetic cross of the two par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 57 publications
(53 reference statements)
2
22
0
Order By: Relevance
“…One example was the major peak on chromosome 8 (represented by marker Py20321) that was significantly linked to genes functioning in hematopoiesis or RBC surface molecules, including the gene encoding glycophorin A (Figure 4A and 4D). Examination of the MS marker inheritances among the progeny typed previously (Li et al, 2011; Pattaradilokrat et al, 2014) found two progeny (G001#4 and F117#2) having crossovers between MS marker Py2669 and Py20322 at the locus (~53.5 kb apart), which was responsible for the decline of LOD scores in the flanking regions (Figure 4E). The normalized log2 expression signal of glycophorin A for F117#2 was −0.44, similar to that of 17XNL (−0.08), whereas G001#4 was −3.81, more similar to that of N67 (−1.6) (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 81%
“…One example was the major peak on chromosome 8 (represented by marker Py20321) that was significantly linked to genes functioning in hematopoiesis or RBC surface molecules, including the gene encoding glycophorin A (Figure 4A and 4D). Examination of the MS marker inheritances among the progeny typed previously (Li et al, 2011; Pattaradilokrat et al, 2014) found two progeny (G001#4 and F117#2) having crossovers between MS marker Py2669 and Py20322 at the locus (~53.5 kb apart), which was responsible for the decline of LOD scores in the flanking regions (Figure 4E). The normalized log2 expression signal of glycophorin A for F117#2 was −0.44, similar to that of 17XNL (−0.08), whereas G001#4 was −3.81, more similar to that of N67 (−1.6) (Supplementary Table 2).…”
Section: Resultsmentioning
confidence: 81%
“…Among the RMPs, P. yoelii has been used as an animal model for vaccine development and for studying the genetic basis of parasite invasion and virulence [ 7 9 ]. Recently, various genetic markers [ 10 12 ] and genetic crosses have been reported for mapping important traits, such as red blood cell (RBC) invasion, parasite growth, and host cytokine/chemokine levels in P. yoelii infection [ 8 , 13 , 14 ] using clonal P. yoelii lines that exhibit wide variation in disease genotypes [ 9 , 15 , 16 ]. However, genetic mapping can only link chromosome segments containing various candidate genes to a phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…There are three subspecies of Plasmodium yoelii ( P. yoelii yoelii , P. yoelii nigeriensis , and P. yoelii killicki ) and a number of strains and clonal lines (all lines used in this study are cloned parasite lines) that exhibit wide variation in disease phenotypes, from mild disease to lethal infection [8,9]. For example, P. y. yoelii strain 17XNL (17XNL), the most common laboratory strain and the genome reference strain of P. yoelii [10], is a non-virulent parasite that causes a mild infection, whereas P. y. yoelii strain YM (YM) and P. y. nigeriensis N67C (N67C) parasites are highly virulent and generally produce lethal diseases [8,9,11]. Characterization of the genetic differences between lethal and non-lethal parasite lines may lead to discovery of molecular markers of severe malaria phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Characterization of the genetic differences between lethal and non-lethal parasite lines may lead to discovery of molecular markers of severe malaria phenotypes. Indeed, recent mapping studies have linked parasite growth-related virulence and host cytokine/chemokine levels to various chromosomal loci [9,11,12]. However, these mapping studies largely relied on typing individual genetic markers such microsatellites (MS) markers [9].…”
Section: Introductionmentioning
confidence: 99%